Pharmacognostical study of Chorisia insignis HBK. grown in Egypt - Taha EI Alfy; Salma El Sawi; Sahar Abd El Tawab; Doaa Moawad (Faculty of Pharmacy, Cairo University, 2012)
Chorisia insignis HBK. is a perennial deciduous plant native to South America. This study presents the macro and micromorphological features of the plant and the determination of its pharmacopoeial constants (Moisture = 12.80%, Total ash = 11.72%, Water soluble ash = 9.24%, Acid insoluble ash = 0.16% and Crude fibre = 20.33%). Furthermore, the DNA of the plant was extracted from leaf samples and analyzed by polymerase chain reaction (PCR) using 12 decamer primers. The DNA fingerprint showed a total of 95 fragments. Protein electrophoresis was carried out using SDS-PAGE (sodium dodecyl sulphate polyacrylamide gel electrophoresis) technique to monitor the seed storage protein expressed by the active genes of the whole genomic DNA of C. insignis HBK. The data obtained revealed the presence of 20 sharp protein bands having a wide range of molecular weights. The percentage of protein in the seeds was found to be 26.83% as determined using micro-Kjeldahl method. Analysis of the total amino acids content of the seeds revealed the identification of 15 amino acids, mainly glutamic acid (26.71%), aspartic acid (11.98%) and glycine (11.00%).